Clinical and epidemiological features of chronic Trypanosoma cruzi infection in patients with HIV/AIDS in Buenos Aires, Argentina - Benchetrit, Andrés Guillermo (2018)
Fil: Benchetrit, Andrés Guillermo. Hospital de Enfermedades Infecciosas Dr. Francisco Muñiz; Argentina.